DETERMINATION OF SIMULTANEOUS SULFAMETHOXAZOLE AND TRIMETHOPRIM BY ULTRAVIOLET SPECTROPHOTOMETRY WITH MEAN CENTERING OF RATIO SPECTRA - Muchlisyam; Tr, Pardede; R, Satiawan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Mean centering of ratio spectra (MCR) is analysis method for determination levels of mixture that has maximum wavelength is overlapping, and without preliminary separation. The purpose of this study is a determination of sulfamethoxazole (SLF) and trimethoprim (TRM) mixture by ultraviolet spectrophotometry with MCR. Methods: Absorption spectra of each drug were recorded and divided by the corresponding concentration of divisor, and the ratio spectra were then mean centered. SLF and t TRM concentrations were determined from calibration graphs by measuring at obtained maximum wavelengths 256 nm for SLF and 288 nm for TRM. Result: The result determination of SLF and TRM content in tablet S was 103.31Â±0.34% and 96.588Â±2.13%, respectively, result of validation method was fulfilled, percentage recovery for SLF was 101.24% and relative standard deviation (RSD) was 0.41%, and percentage recovery for TRM was 100.89% and RSD was 0.96%. Conclusion: The determination simultaneous by ultraviolet spectrophotometry of MCR was found to be accurate, precise, simple, and rapid method and can be used for SLF and TRM mixture.